2017
DOI: 10.1186/s12889-016-3999-4
|View full text |Cite
|
Sign up to set email alerts
|

White rice intake and incidence of type-2 diabetes: analysis of two prospective cohort studies from Iran

Abstract: BackgroundRefined grains and white rice have been associated with elevated risk of type 2 diabetes mellitus (T2DM). In this study, we sought to quantify the effect of white rice intake on incident T2DM in two prospective population-based cohort studies from Iran, where white rice is one of the main staple.MethodsWe used follow-up data from 9,182 participants from Golestan Cohort Study (GCS, 2004–2007, conducted mainly in rural areas) and 2,173 from Tehran Lipid and Glucose Study (TLGS, 2004–2006) who did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…Data from two prospective studies from Iran reported opposing results ( 21 ). While data from Tehran showed significantly higher risk for >250 g/day of white rice, the Golestan Cohort Study showed no significant increase in risk at 210 g/day intake of white rice ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from two prospective studies from Iran reported opposing results ( 21 ). While data from Tehran showed significantly higher risk for >250 g/day of white rice, the Golestan Cohort Study showed no significant increase in risk at 210 g/day intake of white rice ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from two prospective studies from Iran reported opposing results ( 21 ). While data from Tehran showed significantly higher risk for >250 g/day of white rice, the Golestan Cohort Study showed no significant increase in risk at 210 g/day intake of white rice ( 21 ). A lack of association between white rice intake and incident diabetes was also reported in a study conducted in southern Spain ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mente et al recently showed that increased carbohydrate intake is associated with lower LDL-C and HDL-C and also higher TG and TC/HDL-C ratio [ 48 ]. Additionally, among Iranians, intake of carbohydrate, especially white rice, that was associated with incident T2DM, is high [ 49 ]. Third, because physical activity level was assessed with the lipid research clinic in the first phase of the TLGS and by the modifiable activity questionnaire from the 2nd phase [ 23 ], we did not enter this variable in our data analysis, although physical inactivity was not shown as an independent predictor for incident T2DM among Tehranian adults [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, another study revealed that the GI of white rice depends on the proportion of the amylose content of the grain in addition to the cooking time, and the GI value of white rice has been reported to be higher than that of brown rice and other whole grains (Foster-Powell, Holt, & Brand-Miller, 2002). Other two prospective cohort studies in Iran observed a doubling of diabetes risk associated with > 250 g of white rice intake in Tehran Lipid and Glucose Study (TLGS) when compared to Golestan Cohort Study (GCS) (Golozar et al, 2017). Similarly, our current study has reported that individuals with PWS highly consumed white rice (1071 g, 1370 kcal/day) matched with another daily intake of foods.…”
Section: Discussionmentioning
confidence: 99%